With united strength H.H. Shaikh Zayid Bin Sultan Al Nahyan, the leader and the nation (Emirates Center for Strategic Studies and Research, 2013)
Against the backdrop of the British withdrawal from the Arabian Gulf region, it was H.H. Shaikh Zayid who accomplished the complex task of unifying the erstwhile Trucial States, creating the only thriving federal state in the Middle East. While fulfilling his personal destiny as the chosen leader, H.H. Shaikh Zayid strengthened the nation by uniting disparate tribal groups and sustained it against formidable challenges. He pioneered the modernization of the country and ultimately realized his dream of an effective framework for collaboration with neighboring Gulf states. The UAE has since become a constructive force within the region and beyond, exemplifying the principles of national unity, regional solidarity, international cooperation and religious tolerance